Design of an IoT-Based 4-Channel 5V Relay Controller Using WiFi and Smartphone Integration - Samsudin Samsudin; Abdullah Abdullah; Abdul Muni; Niko Niansyah (Sistemasi: Jurnal Sistem Informasi)
The development of remote-controlled electrical device systems has become increasingly essential, particularly in supporting the transition toward a green economy. This IoT-based system, built on the NodeMCU microcontroller, enables real-time monitoring and control of electrical power usage, helping reduce energy waste and minimize carbon emissions caused by inefficient electricity consumption. This study aims to develop an Internet of Things (IoT)-based system for controlling electrical devices using a NodeMCU microcontroller integrated with the Telegram bot platform. The system utilizes a WiFi network to receive and execute user commands in real time. The development process follows the Multimedia Development Life Cycle (MDLC), while the programming is conducted using the Arduino IDE in C++. Testing on various devices—including Samsung Galaxy, iPhone, and Xiaomi Redmi smartphones—demonstrated the system’s ability to respond to commands within 0.45 to 0.82 seconds, with a deviation tolerance of ±0.15 seconds, depending on the specific WiFi network used. No overheating occurred under maximum load conditions. Overall, the system met performance criteria in terms of speed, consistency, and reliability. The primary advantages of the system include its universal chat-based interface, low cost, and simple design, accessible from any geographical location with a stable internet connection. However, the system is limited by its dependence on electricity supply and WiFi stability. Therefore, the implementation of this system in smart homes is recommended with the support of a backup power source to improve reliability. In conclusion, the system not only fulfills technical performance requirements but also contributes to energy efficiency in alignment with green economy principles.